Estudo da audição de músicos de rock and roll - Maia, Juliana Rollo Fernandes (2006)
When we think about music, it is difficult to imagine that it may cause a hearing damage. Nevertheless, when played at high sound pressure levels, music can be harmful to man. Rock and roll is performed in excessive sound pressure levels. Several studies have demonstrated that rock concert s sound levels can range from 100 to 115 dB (A), with peak levels of 150 dB (A). Objective: to study the rock and roll musician´s hearing, analyzing the results of the audiological evaluation and verifying whether time of musical exposure is a source of variability. Methods: a questionnaire with objective of raising the personal data, health, exposure to amplified music, complaints and variable was applied to the musicians, that could influence the found results. 23 rock and roll musicians (46 ears) were evaluated by means of pure tone audiometry, immitance audiometry and transient/distortion product evoked otoacoustic emissions. Results: the main auditory complaints were: intolerance for loud sounds (48%) and tinnitus (39%). The results also revealed that all musicians (100%) presented hearing thresholds within normal range; however, 19 ears (41%) had presented audiometric notch in 4000-6000 Hz. 100% of the ears presented type A tympanogram and acoustic reflexes present in 500, 1000 and 2000 Hz bilaterally. In 4000 Hz, 65,2% of the reflexes were present and 34,8%, absent. TEOAEs were presented in 39% and absent in 61%. In the OAEPD test more than 50% of the ears had response presence on the evaluated frequencies. Conclusions: the results had shown that although hearing loss was not present in the studied population, already exists alteration in the OAE register, which suggests alteration of the cochlear function. In relation to the exposure time, the results demonstrated that the musicians with career time over 10 years statistically presents significant difference compared to those with career time minor than 10 years